Role of Hypoxia-Inducible Factors in the Development of Liver Fibrosis - Roth, Katherine J. (Cell Mol Gastroenterol Hepatol, 2015)
Liver fibrosis remains a significant clinical problem in the United States and throughout the world. Although important advances in the understanding of this disease have been made, no effective pharmacologic agents have been developed that directly prevent or reverse the fibrotic process. Many of the successes in liver fibrosis treatment have been targeted toward treating the cause of fibrosis, such as the development of new antivirals that eradicate hepatitis virus. For many patients, however, this is not feasible, so a liver transplant remains the only viable option. Thus, there is a critical need to identify new therapeutic targets that will slow or reverse the progression of fibrosis in such patients. Research over the last 16 years has identified hypoxia-inducible factors (HIFs) as key transcription factors that drive many aspects of liver fibrosis, making them potential targets of therapy. In this review, we discuss the latest work on HIFs and liver fibrosis, including the cell-specific functions of these transcription factors in the development of liver fibrosis.